Dynamic analysis of elevated tanks having various supporting frame configurations - Gate’a , Mawahib A.; Atalla, Dr. Abdulamir (University of Thi-Qar Journal, 2019)
Liquid storage tanks and especially the elevated tanks are structures of high importance which are considered as main lifeline elements in modern life. As earthquakes are the most powerful and dangerous loads that storage tanks may suffer, the vibrated tank with or without a contained liquid is so critical case so that researchers and designers must give high interest while studying this type of structures. In this work a free vibration analysis had been carried out for an empty elevated concrete cylindrical liquid storage tank supported on a frame consisted of four stories. Four values of height of the frame are explored; 12, 16, 20 and 24m and four values of column angle of inclination; 0°, 2.38°, 4.76°, 7.125° measured from the vertical are examined. The tanks are modeled by the finite element method and the analysis is conducted using ANSYS 11. The natural frequency is found to decrease with increasing in frame height and angle of frame inclination due to stiffness decrement of the supporting frame. A forced vibration analysis is also done on a selected case of elevated tank under three filling percentages: 0%, 50% and 100% .The seismically excited tank has a height of 15.9m and is subjected to Kocaeli earthquake in Turkey, 1999. The dynamic response including the maximum stresses and displacements is determined and discussed.